Lateral and oblique interbody fusions in degenerative and isthmic spondylolisthesis - Ganesh Swamy (Indian Spine Journal, 2021)
While symptomatic degenerative and isthmic spondylolisthesis cause pain and surgical management improves quality of life, it is less clear which surgical strategies are most helpful. In this review, we seek to outline the accuracy and reliability of classification schemes and suggest how machine-learning tools can potentially help identify optimal surgical strategies for individual patients. In addition, we examine the role of new surgical strategies in degenerative and isthmic spondylolisthesis, namely using lateral and oblique interbody fusions. Herein we discuss lateral and oblique interbody fusions in spondylolisthesis within a framework of accepted surgical goals, sagittal plane balance considerations, and cost-effectiveness.